PEMANFAATAN FUNGSI OTAK SECARA SEIMBANG DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Lis Yulianti Siregar (IAIN Padangsidimpuan, 2021)
The problem in this study is the mismatch of the balance of the work function of the right brain and left brain in learning Islamic Religious Education. Ideally, when there is a balance, the learning will be able to run effectively and pleasantly, but in fact there are still students who feel bored and sleepy while studying, there are even students who leave the room while learning is taking place. The research objective was to determine the factors that cause the balance of brain function utilization to be unbalanced. The research method used is library research or library research, namely a review of scientific works. Data collection techniques using content analysis techniques and constant comparative analysis. The results showed that the balanced use of brain function is a process, method, or action of brain function in learning according to the same amount of use. The balance of brain functions will facilitate a pleasant learning process and create effective and efficient learning. The use of balanced brain function in learning can be done by using learning media such as visual media, audio-visual media, and computer-based media, and several learning strategies that are tailored to the workings of the brain so that they can be balanced in their utilization which is applied by the teacher according to the material presented. such as active learning strategies, innovative, creative, effective and fun for students.